The Interaction between Osmotic- and Pressure-induced Water Flow in Plant Roots - Fiscus, Edwin L. (1975)
This paper presents a general model for coupled solute and water flow through plant roots based on the thermodynamics of irreversible processes. The model explains in a straight-forward manner such experimentally observed phenomena as changes in root resistance, increased solute flux, and apparent negative resistance, which have been reported for root systems under the influence of a hydrostatic pressure gradient. These apparent anomalies are explained on the basis of the interaction between the osmotic and hydrostatic driving forces and the well known “sweeping away” or dilution effect. We show that with a constant hydraulic conductivity the only features necessary to explain these phenomena are some type of membrane or membranelike structure and a mechanism for actively accumulating solutes.